Construction of Restorative Justice Law Enforcement by The Prosecutor: Development Law Theory Perspective - Ganiviantara Pratama (Fakultas Hukum Universitas Lampung, 2022)
The development and dynamics of society is very complex. Complexity also includes law enforcement in Indonesia. There are so many problems: first, prison overcapacity; second, handling small crimes and legal action against children and narcotics problems are a series of problems that exist in Indonesia. Restorative Justice is here to show changes in all these legal problems. This writing is a normative juridical writing with a conceptual approach (Conceptual Approach) and a statutory approach (Statute Approach). This writing is presented in a qualitative descriptive. The results of this paper discuss specifically about the urgency of Restorative Justice law enforcement in the Indonesian criminal justice legal system and the form of social engineering construction of restorative justice law enforcement by the prosecutor's office. The form of social engineering initiated by the prosecutor's office as an active actor in law enforcement is expected to form a more humane prosecutor's institution and improve its image as a law enforcement agency with integrity.